Implementasi Sistem Pendukung Keputusan Berbasis Internet of Things (IoT) Untuk Menentukan Kesehatan Tanaman Bunga Kertas Menggunakan Metode Simple Additive Weighting (SAW) - Asmaul Husna; Fatma Sari Hutagalung (Universitas Methodist Indonesia, 2024)
Ornamental plants are plants that are in great demand these days because of their beauty and attractiveness. Ornamental plants are an important aspect because they are able to maintain environmental health, the more ornamental plants the better it is also to beautify the environment. In this research, a determination process is carried out to determine the health of ornamental plants, one of which is Bougenville Flower or commonly referred to as paper flower, which is an ornamental plant whose existence is quite popular among the public and is widely spread in various regions in Indonesia. The method used in this research is the Simple Additive Weighting (SAW) method to rank alternatives. The criteria used are 3 namely air temperature, air humidity, and soil pH, while the alternatives used are 10 paper flower ornamental plants with the aim of ranking the best or healthy paper flower plants from the samples tested. Implementation with the SAW method produces recommendations for paper flower ornamental plants, namely A3 or paper flower 3 accompanied by the results of ranking values with a value of 0.992 which is the highest value compared to other alternatives. This research has also been calculated using Confusion Matrix with an accuracy test result of 60%.